KAJIAN KARAKTERISTIK DINAMIKA TANAH TERHADAP RESIKO KERAWANAN SEISMIK DAN DAMPAKNYA TERKAIT RENCANA TATA RUANG WILAYAH DI KOTA MATARAM BAGIAN TIMUR - , Icha Untari Meidji ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Has been done a research of microtremor in the eastern part of Mataram City in the Lombok Island. This study was based on analysis data of microtremor with additional data from monitoring earthquake occurence by United State Geological Survey (USGS) and boring data in Lombok Island, especially in the city of Mataram. This study was conducted to analyze the vulnerability of earthquakes impact based on the caracteristics of soil dynamics such as the thickness of sediment layer using data Vs30 and elipticity inversion. seismic vulnerability index (Kg), ground shear strain (Î³) and the Peak Ground acceleration (PGA) that useful for Urban Land Plan for Mataramâs goverment. The results showed that in the eastern part of the Mataram City has distribution of thickness sediment layer is 12.8 meters to 57.2 meters, the distribution of seismic vulnerability index values ranged from 1.65 to 22.80, the distribution of PGA values of surface soil layer ranged between 299.59 gal to 850.92 gal and distribution of ground shear strain values ranged from 2.41 Ã10-4 to 3.56 Ã 10-3. The Seismic vulnerability map shows that the eastern part of Mataram City has been identified with the scale of the seismic vulnerability from low (risk category I, II, III and IV), medium (risk category I and II) to high scale (risk category I). Subdistrict Selaparang has seismic vurnerability medium scale and high scale, Subdistrict Cakranegara has seismic vurnerability medium scale and low scale, as well as District Sandubaya has seismic vulnerability scale of low, medium and high scale in some locations. Keyword: Microtremor. PGA, Vs30, Seismic Vulnerability Index, Ground Shear Strain, HVSR, Mataram City